Flow injection and related techniques in blood studies for clinical screening and analysis: A review - Supaporn Kradtap Hartwell (2018)
Blood studies for clinical screening/analysis are geared toward point of care testing. Flow based techniques have expanded their applications with unique approaches that may be adaptable for use as alternative disease screening/diagnosis. Many newly developed systems for solution based chemical analysis can be easily adapted for use with plasma and serum. However, cell and intracellular analyses are different. Blood cell analyses require a particular way of sample introduction and detection. This review emphasizes the applications of flow based techniques, especially those that were coupled with FI/SI, in clinical studies through analysis of red blood cells and their intracellular substances. © Taylor & Francis Group, LLC.